Bacillus Strains Isolated from Soryz are Producers of Proteolytic Enzymes - Gudzenko, O.V.; Avdiyuk, K.V.; Varbanets, L.D.; Pasichnyk, L.A.; Reshetnikov, M.V.; Гудзенко, О.В.; Авдіюк, К.В.; Варбанець, Л.Д.; Пасічник, Л.А.; Решетніков, M.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
In recent years, the attention of researchers has been attracted by bacterial strains isolated from soryz, a new grain crop that combines the advantages of rice STRArelevant and promising field of research for several reasons. First, plants are a rich source of microorganisms that produce a wide range of proteases with different properties useful for industrial and biotechnological applications. Second, since the cultivation of soryz does not require the use of chemicals, the protease producers obtained from it are more environmentally friendly than proteases isolated from plants that require the use of chemicals. Therefore, the purpose of this work was to conduct a screening among strains isolated from soryz, producers of proteases (in particular, keratinases, elastases, fibrinases, and fibrinogenases), important for industry and medicine. Methods. The objects of the study were 13 cultures of Bacillus isolated from soryz. Different types of nutrient media were used for cultivating strains. To determine keratinase activity, cultures were grown on a nutrient medium containing 0.5% defatted chicken feathers as sole sources of carbon and nitrogen. To study fibrinolytic, fibrinase, and elastase activities, a nutrient medium containing maltose and gelatin as a carbon source and ammonium sulfate as a nitrogen source was used. The cultures were grown under conditions of submerged cultivation in large test tubes at 28 °C, with a nutrient medium stirring rate of 232 rpm for 4 days. The keratinase activity was assessed by UV absorption at 280 nm of hydrolysis products of keratin-containing materials. The caseinolytic (total proteolytic) activity was determined by the Anson method. The disulfide reductase activity (DSRA) was measured spectrophotometrically at 412 nm by evaluating the yellow sulfide formed during the reduction of 5,5’-dithiobis-(2-nitrobenzoic acid) (DTNB). The enzyme activities were studied in the culture liquid supernatant. Results. It was shown that 10 out of 13 investigated cultures synthesized keratinase, the level of which varied from 3–5 U/mL (cultures Bacillus sp. 21036, B. vallismortis ASV3, Bacillus sp. 21038, Bacillus sp. 21046, Bacillus sp. ASV1, and Bacillus sp. 21134) to 14 U/mL (Bacillus sp. 21096). All cultures that showed keratinase activity also synthesized disulfide reductase (DSR). DSRA indicator differed among the studied strains: it was the highest in B. subtilis B4 (52 µmol/min) and the lowest in B. vallismortis ASV3 (17 µmol/min) and Bacillus subtilis 21040. The level of the total proteolytic (caseinolytic) activity was very low, and only Bacillus sp. 21096, B.  subtilis Б4, and Bacillus sp. 21029 showed 0.013–0.015 U/mL of activity. Insignificant fibrinolytic activity, the level of which varied from 1.13 to 5.6 U/mL was shown by 8 out of 13 studied Bacillus strains. All cultures, except for B.  subtilis B4, Bacillus sp. 21029, and Bacillus sp. 21134, showed fibrinogenolytic activity, but their indicators differed significantly. Bacillus sp. 21095 culture had the highest activity (15 U/mL). All studied cultures, except for Bacillus sp. 21134, showed elastase activity, the level of which was from 5.2 to 20.3 U/mL. Its highest indicators were noted for cultures of B. subtilis 21040 (20.3 U/mL), Bacillus sp. ASV1 (18.8 U/mL), Bacillus sp. 21036 (17.3 U/mL), and Bacillus sp. 21066 (13.02 U/mL). Conclusions. The studied representatives of the genus Bacillus, isolated from the rhizosphere of the agrocenosis soil of soryz, can be promising for further research as producers of keratinases, fibrinogenases, and elastases due to their catalytic properties.